TANTANGAN DAN MASALAH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN METODE KOOPERATIF (COOPERATIVE LEARNING) PADA SISWA SMP NEGRI 1 SUNGKAI UTARA - Chandra, Adika; Westika, Ria; Patimah, Siti; Afifatun , Siti; Sajdah , Meilisa (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Cooperative learning is a learning method that is carried out by working together between students, so that later students do not only achieve success individually or defeat each other. And the process describes the problems and challenges faced by Islamic religious education teachers in internalizing the values of Islamic religious education to students at school. The challenges and problems that arise are caused by the times, even many outside cultures that must be filtered first because they are not in accordance with the values of Islamic education. The data analysis technique in this research uses qualitative descriptive methods. Qualitative research is research that aims to understand the phenomena experienced by the research subject. in this study will describe how the teacher's strategy in internalizing the values of Islamic religious education to students. There are three aspects included in the values of Islamic education, namely: moral values (morals to God, morals to others and morals to oneself), belief values (faith in God and His messengers), and worship values. The strategies carried out in internalizing the values of Islamic religious education include several stages, namely: the value transformation stage, the value transaction stage, and the internalization stage.